2018
DOI: 10.1111/vsu.12930
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating veterinary student skill acquisition on a laparoscopic suturing exercise after simulation training

Abstract: Simulation offers an adequate platform for the standardized training of laparoscopic skills in veterinary students and likely novice laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…The findings of this study are important because laparoscopic simulators have been shown in both human and veterinary medicine to improve core laparoscopic skills, allowing for shorter surgical times and better economy of movement. Finding time for simulator training appears to be a concern for current residents, and, with mandatory use of simulators required by fewer than one in five of the programs that have simulators, it is probable that simulators are not being widely used.…”
Section: Discussionmentioning
confidence: 94%
“…The findings of this study are important because laparoscopic simulators have been shown in both human and veterinary medicine to improve core laparoscopic skills, allowing for shorter surgical times and better economy of movement. Finding time for simulator training appears to be a concern for current residents, and, with mandatory use of simulators required by fewer than one in five of the programs that have simulators, it is probable that simulators are not being widely used.…”
Section: Discussionmentioning
confidence: 94%
“…Training programs in human and veterinary laparoscopy tend to involve repetitive, self-directed, or guided practice over several weeks. 3,22,30,43,44 This format reflects evidence that laparoscopic performance improves progressively with practice and that ample, deliberate practice is required to reach expertise. 3,45 By contrast, the training protocol selected for this study consisted of 4 days of multimodal training and supervised practice with a low instructor-toparticipant ratio.…”
Section: Discussionmentioning
confidence: 99%
“…While alternatives do exist for providing ex‐vivo training, the majority of respondents felt that this would not, or would only partially help gain clinical skills and experience. While simulator‐based training has been shown to improve clinical skills, particularly in fields such as laparoscopy, 24–26 they are seldom available to residents at their institutions. The above strategies could contribute toward the maintenance of skills during periods where a dramatic drop in case load is experienced, and provision should be considered by institutions.…”
Section: Discussionmentioning
confidence: 99%